"Philosophy, ethics and a common humanity: essays in honour of Raimond Gaita" - "Cordner, Christopher (ed.)" (London, 2011)
The work of Raimond Gaita, in books such as Good and Evil: An Absolute Conception, A Common Humanity and The Philosopher$1 (Bs Dog, has made an outstanding and controversial contribution to philosophy and to the wider culture. In this superb collection an international team of contributors explore issues across the wide range of Gaita$1 (Bs thought, including the nature of good and evil, philosophy and biography, the unthinkable, Plato and ancient philosophy, Wittgenstein, the religious dimensions of Gaita$1 (Bs work, aspects of the Holocaust, and aboriginal reconciliation in Australia.s
Keywords: "Gaita, Raimond"